Study of Nusantara Islamic Manhaj - Sabri; Miftahul Huda; Zulkarnain; Muhammad Maghfurrohman (al-Afkar, Journal For Islamic Studies, 2025)
The phenomenon of Middle Eastern Islam being destroyed by the brutality of fundamentalist ideologies, thick with shadows of fanaticism and orthodox paradigms, has given rise to the urgency of studying the methodology and thought of Nusantara Islam from ontological, philosophical, and axiological perspectives.So that readers can see an explanation of why Nusantara Islam becomes the antithesis of transnational ideological products and fundamentalist doctrines that reject the indigenization of Islam in Indonesia. In fact, Islam in Indonesia entered through the Sufi path, where the process of acculturation between Islamic traditions and local traditions through a cultural approach created an Islam that is rahmatan lil ‘alamin, such as being friendly, wise, polite, cool, and open.where such characteristics of Islam were actually very well accepted by the people of the archipelago, who were predominantly followers of Hindu-Buddhism at that time.